Prostate Cancer Diagnosis PSA, Biopsy and Beyond - Jones, J. Stephen. (Current Clinical Urology, 2013)
Based on the highly successful first edition of Prostate Biopsy: Indications, Techniques, and Complications, this new volume presents new concepts that have emerged in answer to current questions from its audience. Many new perspectives and technologies are presented, many from the authors internationally recognized work on the topic. Substantial developments in techniques and complications are explored in detail. The chapter authors comprise a complete spectrum of specialists in their respective subject areas. All authors are internationally accepted as the premier authorities on their chosen topics. Prostate Cancer Diagnosis: PSA, Biopsy, and Beyond presents new data on the controversial issue of PSA screening and thresholds as indication to perform biopsy. Office based transrectal saturation biopsy is covered in detail. Other topics explored include template guided biopsy and image-guided biopsy as well as a completely new paradigm for prevention of complications. Prostate Cancer Diagnosis: PSA, Biopsy, and Beyond will be of great value and utility to all practicing urologists.